Which dimensions of food-related lifestyle are likely to be associated with obesity in Italy?. Issue 3 (8th February 2013) - Saba, Anna; Cupellaro, Elena; Vassallo, Marco
Abstract: Objective: To compare obese v . non-obese consumers in terms of their general food-related lifestyles and to explore possible food-related factors affecting obesity in Italy. Design: The data were collected using a self-completion questionnaire. Data included sociodemographic information, measures of the Food-Related Lifestyle scale (FRL) and self-reported weight and height. A logistic regression model was fitted for the sample with obesity as the dependent variable and sociodemographic characteristics and FRL dimensions as the independent variables. Setting: The survey was carried out in Italy between October and November 2010. Subjects: One thousand respondents were recruited with equal quotas for men v . women. The sample was representative of the Italian population in term of age groups and geographic areas. The participants were over 18 years of age and were solely or jointly responsible for the family's food shopping. Results: Our analyses revealed that sociodemographic, economic and cultural variables affect the increasing rate of obesity in Italy. Obese respondents appeared to find more enjoyment from shopping and interest in cooking compared with non-obese ones. Moreover, they were more likely to find self-fulfilment in foods. However, obese respondents appeared to be less interested in the nutritional content of foods, suggesting their weak involvement in nutritional aspects when they eat. In fact, the obese respondents gave preference to snacks over meals. Conclusions: The outcome of the study would suggest that in targeted interventions for public health purposes in order to address obesity, attention should be placed on the role that food plays in obese consumers' lives.